Different effects of two N-methyl-D-aspartate receptor antagonists on seizures, spontaneous behavior, and motor performance in immature rats - Mares, Pavel; Mikulecká, Anna (Epilepsy & behavior, 2009)
Typical N-methyl-D-aspartate (NMDA) receptor antagonists exhibit anticonvulsant action and unwanted effects, even in developing rats. Therefore, we studied the actions of the low-affinity, noncompetitive antagonist memantine and the NR2B-specific antagonist ifenprodil. Seizures (minimal clonic and generalized tonic-clonic) were elicited with pentylenetetrazol (100mg/kg subcutaneously) in rats 7, 12, 18, and 25 days old pretreated with memantine (2.5-40 mg/kg intraperitoneally) or ifenprodil (10-60 mg/kg intraperitoneally). The effects of both drugs were studied in open field and motor performance tests in 12-, 18-, and 25-day-old rats. Memantine suppressed generalized tonic-clonic seizures in all age groups; minimal seizures were potentiated. Ifenprodil abolished the tonic phase of generalized tonic-clonic seizures in 7-, 12-, and 18-day-old rats only; minimal seizures remained untouched. Memantine induced locomotor hyperactivity and compromised motor performance in all age groups. Ifenprodil exerted these effects only in 12-day-old rats; older animals were less active in open field tests. Memantine exhibits both anti- and pro-convulsant and behavioral effects typical of NMDA antagonists. Ifenprodil exerted the same effects in 12-day-old rats, but its anticonvulsant action in 18-day-old rats was accompanied by a decrease in locomotion.
Keywords: učení; posturální rovnováha; Behavior, Animal; memantin; Piperidines; záchvaty; konvulziva; Rats, Wistar; Psychomotor Performance; psychomotorický výkon; orientace; vztah mezi dávkou a účinkem léčiva; Epilepsy, Generalized; Hand Strength; síla ruky; potkani Wistar; Seizures; piperidiny; Anticonvulsants; Postural Balance; epilepsie generalizovaná; krysa rodu Rattus; Convulsants; Learning; Animals; Orientation; Memantine; Pentylenetetrazole; zvířata; pohybová aktivita; Rats; antikonvulziva; Motor Activity; chování zvířat; antagonisté excitačních aminokyselin; pentylentetrazol; Dose-Response Relationship, Drug; Receptors, N-Methyl-D-Aspartate; receptory N-methyl-D-aspartátu; Excitatory Amino Acid Antagonists